Nanosilver fluoride as a caries arresting agent in children: A systematic review and meta- analysis - Shikha Choubey; Amol Patil; Abhinav L Talekar; Dheeraj Kalra (Wolters Kluwer Medknow Publications, 2022)
Background: Dental caries is one of the most common concerns in oral health of children. Arresting these lesions is a treatment which is gaining momentum as against conventional restorative approaches. Aim: The aim is to evaluate the efficacy of nanosilver fluoride (NSF) as a caries arresting agent in primary teeth or first permanent molars in children. Design: The protocol for the systematic review has been registered with PROSPERO database (CRD42020162386). Several databases, such as PubMed®/MEDLINE, Web of Science™, Scopus®, Google Scholar, LILACS, Cochrane Library, ProQuest, and BBO, were searched for randomized controlled trials (RCTs) which evaluated the arrestment of caries, in primary teeth and first permanent molars in children, with a minimum follow-up of 6 months. The Risk of Bias tool by Cochrane reviews system software, Revman 5.4.1, was used for quality assessment of the included RCTs. The quality evaluation was done using the GRADE approach. Heterogeneity was assessed using Cochrane's Q and I2 statistics. Results: Five studies were included for qualitative and quantitative analysis. The Risk Ratio for NSF versus active control group was assessed to be 1.09 (0.93-1.28) with 95% Confidence Interval and for placebo control was 0.49 (0.35-0.67). Conclusion: NSF shows promise as a caries arrestment agent when applied in primary teeth. PROSPERO Registration: This review was registered with the PROSPERO database (CRD42020162386)